KLASIFIKASI TINGKAT KEPUASAN MAHASISWA TERHADAP FASILITAS KAMPUS MENGGUNAKAN METODE ID3 - Nurtiani, Devy Natalia; Saputra, Rizal Adi (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This research explores the level of student satisfaction with campus facilities using the ID3 (Iterative Dichotomiser 3) method in forming decision trees. The main focus of this research is to identify factors that influence student satisfaction with various facilities on campus such as libraries, computer laboratories, classrooms, sports facilities, and campus facilities in general. Data from 500 students were obtained from questionnaires and used as a basis for forming a decision tree model. The model visualization provides a clear picture of the satisfaction level classification pattern. This research details the relationships between attributes and contributes to the understanding of factors that influence student decisions. The results of this research provide an in-depth understanding of the attributes that are most influential in predicting student satisfaction levels. The resulting decision tree reflects an informative classification pattern, providing a basis for improving the quality of campus facilities. Implementation of this model produces 100% accuracy in testing data, indicating the model's success in classifying student satisfaction levels. This research contributes to improving the student experience and supporting decision-making regarding campus facilities at higher education institutions.